Empowering Japanese Beginner Learners’ Writing Proficiency by Enhancing Complex Sentences with E-Modules - Mintarsih, Mintarsih; fanani, urip zaenal; Sopaheluwakan, Yovinza Bethvine; Soepardjo, Djodjok; Juangsih, Juju (Universitas Negeri Semarang, 2024)
The Indonesian Ministry of Education and Culture has implemented an independent learning curriculum in all education-level units since January 2020. Many changes occurred with the implementation of the new curriculum. In independent learning curricula, fostering higher-order thinking skills (HOTS) is crucial, especially when developing complex sentence writing proficiency for beginners. This study aimed to improve beginner Japanese learners' ability to construct complex sentences in written activity by utilizing FlipPdf-Pro-based e-modules. These modules incorporated audio, video, and digital applications, making the learning process engaging and self-paced. The study involved 60 students in their third year who had been studying Japanese for one year in a high school in Malang. This study is classroom research using qualitative descriptive methods. Research data was collected through observation, tests, and questionnaires. Observations indicated enthusiastic participation, and questionnaires revealed that participants comprehended how to construct simple, complex sentences and could apply them effectively in written contexts. Over 80% of participants expressed a positive attitude towards learning through FlipPdf-Pro-based e-modules and recognized the importance of digital media in Japanese language learning. Furthermore, the test results demonstrated the participants' satisfactory ability to write complex sentences, meeting criteria in three key aspects: sentence structure in subordinate clauses, cohesion between main and subordinate clauses using the conjunctive phrase -no toki 'when', and coherence in the meaning of complex sentences. Based on test results, response questionnaires, and observations, these findings confirmed that using FlipPdf-Pro-based e-modules effectively enhances learners' proficiency in writing complex sentences.